Impact of duration of maintenance immunotherapy on the prognosis of locally advanced non-small cell lung cancer treated with chemoradiotherapy - Fan, HuiQi; Guan, Song; Ren, Kai; Li, Xue; Wang, Jun; Bi, Nan; Zhao, Lujun (Frontiers in Oncology, 2025)
PurposeChemoradiotherapy combined with consolidation immunotherapy is the standard of care for unresectable stage III non-small cell lung cancer; however, the optimal number of cycles of consolidation immunotherapy remains unknown. This study aimed to investigate the optimal duration of consolidation immunotherapy after chemoradiotherapy.Materials and methodsWe conducted a real-world, multicenter, retrospective study of patients with unresectable stage III non-small cell lung cancer who underwent consolidation immunotherapy between February 2018 and December 2022 following chemoradiotherapy. The inclusion criteria were as follows: (1) age ≥18 years and Karnofsky Performance Scale (KPS) score ≥70; (2) histopathologically confirmed stage III non-small cell lung cancer; and (3) received consolidation immunotherapy after chemoradiotherapy. The exclusion criteria were as follows: (1) patients with EGFR or ALK gene mutations; (2) history of other cancers; (3) tumor progression prior to immunotherapy; (4) immunotherapy concurrently with chemoradiotherapy; and (5) discontinuation of immunotherapy due to detection of disease progression. Univariate analysis was performed via the Cox proportional risk model. The correlations between immunotherapy duration and survival outcomes were determined via Kaplan–Meier and log-rank analyses. The study endpoints in this study were overall survival (OS) and progression-free survival (PFS).ResultsThe median number of cycles of consolidation immunotherapy was 10 (interquartile range: 4, 19). The 1-year OS rates were 91.3% and 100% for patients with ≤ 10 and >10 cycles of immunotherapy, respectively (P<0.001), and the 1-year PFS rates were 53.4% and 98.4%, respectively (P<0.001). And the 1-year OS rates of patients with ≤ 4, > 4 - ≤ 10, > 10 - ≤ 19, and >19 cycles of consolidation immunotherapy were 89.1%, 93.8%, 100%, and 100%, respectively (≤ 4 vs. 4-10: p=0.068; 4–10 vs. 10-19: p=0.023; 10–19 vs. >19: p= 0.435). The 1-year PFS rates were 48.3%, 59.4%, 96.7%, and 100%, respectively (≤ 4 vs. 4-10: P=0.394; 4–10 vs. 10-19: P=0.002; 10–19 vs. >19: P=0.019). In radiotherapy modality subgroup analyses (stratified by histology, immunotherapy type, and concurrent chemoradiotherapy), immunotherapy cycle number significantly predicted prognosis in all subgroups (all p < 0.05).ConclusionIn patients with locally advanced non-small cell lung cancer who received consolidation immunotherapy after chemoradiotherapy, the number of cycles of immunotherapy was significantly associated with prognosis. These results need to be further validated in a large prospective study.